90Y radioembolization in the treatment of neuroendocrine neoplasms: results of an international multicenter retrospective study - Schaarschmidt, Benedikt Michael Sebastian; Wildgruber, Moritz; Kloeckner, Roman; Nie, James; Wagner, Verena; Braat, Arthur J. A. T.; Lohoefer, Fabian; Kim, Hyun S.; Lahner, Harald; Weber, Manuel; Theysohn, Jens (Journal of nuclear medicine, 2022)
In neuroendocrine neoplasms (NENs), the presence of distant metastases has a severe impact on survival leading to a relevant decrease in the 5-y survival rate. Here, 90Y radioembolization (90Y RE) might be an important treatment option; however, data to support clinical benefits for 90Y RE are scarce. Therefore, the purpose of this study was to analyze the use of 90Y RE in NEN patients with hepatic metastases in an international, multicenter retrospective analysis and assess the potential role of 90Y RE in a multimodal treatment concept. Methods: In total, 297 angiographic evaluations in NEN patients before 90Y RE were analyzed. Baseline characteristics and parameters derived from imaging evaluation and 90Y RE were analyzed. Tumor response was assessed using RECIST 1.1, and survival data were collected. Mean overall survival (OS) between different groups was compared using Kaplan-Meier curves and the log rank test. A P value of less than 0.05 indicated statistical significance. Results: After 90Y RE, the disease control rate according to RECIST 1.1 was 83.5% after 3 mo and 50.9% after 12 mo. OS in the entire population was 38.9 ± 33.0 mo. High tumor grade (P < 0.006) and high tumor burden (P = 0.001) were both associated with a significant decrease in OS. The presence of extrahepatic metastases (P = 0.335) and the type of metastatic vascularization pattern (P = 0.460) had no influence on OS. Patients who received 90Y RE as second-line therapy had a slightly longer but not statistically significant OS than patients who had 90Y RE in a salvage setting (44.8 vs. 30.6 mo, P = 0.078). Hepatic and global progression-free survival after 90Y RE was significantly decreased in heavily pretreated patients, compared with patients with second-line therapy (P = 0.011 and P = 0.010, respectively). Conclusion: 90Y RE could be an important alternative to peptide receptor radionuclide therapy as second-line treatment in patients with progressive liver-dominant disease pretreated with somatostatin analogs.
Im Text ist "90" hochgestellt
Published online Sep. 2, 2021
Gesehen am 28.06.2022